2011
DOI: 10.1074/jbc.m111.231076
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Conversion of Folinic Acid Is Required for Antifolate Resistance

Abstract: Antifolates, which are among the first antimicrobial agents invented, inhibit cell growth by creating an intracellular state of folate deficiency. Clinical resistance to antifolates has been mainly attributed to mutations that alter structure or expression of enzymes involved in de novo folate synthesis. We identified a Mycobacterium smegmatis mutant, named FUEL (which stands for folate utilization enzyme for leucovorin), that is hypersusceptible to antifolates. Chemical complementation indicated that FUEL is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 60 publications
0
37
0
Order By: Relevance
“…A novel determinant identified from this screen was further characterized in a recent report (Ogwang et al, 2011). The M. smegmatis mutant presented in this report exhibits hypersusceptibility to several combinations of trimethoprim/sulfonamides tested (Ogwang et al, 2011). For example, its MIC to trimethoprim/sulfachloropyridazine is 64 fold lower than that of the parental M. smegmatis strain.…”
Section: Potentiation Of Antifolates In Mycobacteriamentioning
confidence: 99%
See 3 more Smart Citations
“…A novel determinant identified from this screen was further characterized in a recent report (Ogwang et al, 2011). The M. smegmatis mutant presented in this report exhibits hypersusceptibility to several combinations of trimethoprim/sulfonamides tested (Ogwang et al, 2011). For example, its MIC to trimethoprim/sulfachloropyridazine is 64 fold lower than that of the parental M. smegmatis strain.…”
Section: Potentiation Of Antifolates In Mycobacteriamentioning
confidence: 99%
“…Using this non-bias screen, the genome-wide collection of antifolate resistance determinants in mycobacteria (mycobacterial antifolate resistome) was found to be composed of fifty resistance determinants (unpublished data). A novel determinant identified from this screen was further characterized in a recent report (Ogwang et al, 2011). The M. smegmatis mutant presented in this report exhibits hypersusceptibility to several combinations of trimethoprim/sulfonamides tested (Ogwang et al, 2011).…”
Section: Potentiation Of Antifolates In Mycobacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Poly-glutamate folate parent m/z is 129 more for one additional glutamate but with the same product ion m/z as the one corresponding to monoglutamate folate. Profiling of the folate derivatives showed that mono-glutamate folates had no change compared to the wild type Mycobacterium smegmatis, but dramatically decreased poly-glutamate 5-formyltetrahydrofolate, which indicates the important physiological role of poly-glutamate 5-formyltetrahydrofolate in the folate metabolism (Ogwang et al, 2011). …”
Section: Targeted Folate Derivatives Quantitation By Tandem Mass Specmentioning
confidence: 99%